2007
DOI: 10.1211/jpp.59.10.0009
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive activity of fexofenadine hydrochloride on nitric oxide production in-vitro and in-vivo

Abstract: The aim of this study was to examine the effect of fexofenadine hydrochloride (FEX), a histamine H1-receptor antagonist, on nitric oxide (NO) production in-vitro and in-vivo. Nasal fibroblasts (5 x 10(5) cells per mL) were stimulated with 25 ng mL(-1) tumour necrosis factor-alpha in the presence of various concentrations of FEX. NO levels in 24-h-culture supernatants were measured by the Griess method and levels of inducible nitric oxide synthase (iNOS) mRNA levels in 12-h-cultured cells were measured by ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The residual cells were stimulated with LPS in the presence of various concentrations of agents in a total volume of 2.0 ml. To prepare culture supernatants, cells were cultured for 24 hours [ 21 ], and the culture medium was removed and stored at -40°C until used. Cells for examination of phosphorylation of mitogen-activated protein kinases (MAPKs), transcription factor activation, inducible NO synthase (iNOS) mRNA expression and iNOS protein were cultured in a similar manner for 2, 4, 8 and 12 hours, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The residual cells were stimulated with LPS in the presence of various concentrations of agents in a total volume of 2.0 ml. To prepare culture supernatants, cells were cultured for 24 hours [ 21 ], and the culture medium was removed and stored at -40°C until used. Cells for examination of phosphorylation of mitogen-activated protein kinases (MAPKs), transcription factor activation, inducible NO synthase (iNOS) mRNA expression and iNOS protein were cultured in a similar manner for 2, 4, 8 and 12 hours, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It was also shown that fexofenadine suppressed NO production in nasal fibroblasts in vitro and in lung tissue of rats in vivo. [27] Takeno et al showed that increased nasal NO levels in AR patients were caused by increased levels of the iNOS isoenzyme form. [28] Kawamoto et al compared iNOS levels of various nasal tissues of patients with AR and the control group.…”
Section: Ent Updatesmentioning
confidence: 99%
“…( Table 3). Interestingly, it has been reported that antihistamines have favorable pharmacological properties on these aspects in vitro [2, [29][30][31][32][33][34][39][40][41][42][43][44][45][46]. Keratinocytes are considered an immunocompetent cell type for the production of cytokines or other biological substances.…”
Section: Key Pointsmentioning
confidence: 99%